Attitude and active payload control: the H∞ revolution. Issue 1 (July 2017) - Pittet, C.; Mignot, J.; Viaud, F.
Abstract: In this paper, the different steps of H∞ control story at CNES for the attitude of satellites and test beds are presented. From early studies in the 90's to industrial operational use in orbit, the way to tune H∞ controllers with respect to the requirements is illustrated. At the beginning, the design of H^ controllers was devoted to control experts who could tune the weighting functions and the solvers parameters to get suitable results. The new tools based on non-smooth optimization gather the power and flexibility of H∞ control and the know-how of engineers in tuning the soft and hard constraints with respect to the requirements. The powerful H∞ optimization can now be used in an operational manner by non-experts which is the definition of a successful transfer of technology.